2020
DOI: 10.21307/jofnem-2020-017
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence and distribution of entomopathogenic nematodes (Steinernematidae, Heterorhabditidae) in Viti Levu, Fiji Islands

Abstract: In Fiji, little or no attention has been given to entomopathogenic nematodes (EPNs) in biocontrol programs due to the lack of awareness about their occurrence and distribution in Fiji. A survey of EPNs was conducted for the first time in Fiji Islands in 2012 and 2013, throughout the eight provinces in Viti Levu to determine the occurrence and distribution across different habitat in Viti Levu. The soil samples from various habitats were collected and assayed for the presence of EPN using Galleria mellonella as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
(62 reference statements)
5
12
0
Order By: Relevance
“…From a total of 50 soil samples collected from peanut and grassland areas, only 5 harbored nematodes indicating a recovery rate of 10%. This low recovery rate is congruent with several previous studies on EPNs recovery in different surveys worldwide (Caoili et al 2018 andKour et al 2020). Several abiotic and biotic factors may likely influence the recovery of nematodes in the soil such as soil texture, moisture, pH, and vegetation (Abate et al 2018 andCampos-Herrera et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…From a total of 50 soil samples collected from peanut and grassland areas, only 5 harbored nematodes indicating a recovery rate of 10%. This low recovery rate is congruent with several previous studies on EPNs recovery in different surveys worldwide (Caoili et al 2018 andKour et al 2020). Several abiotic and biotic factors may likely influence the recovery of nematodes in the soil such as soil texture, moisture, pH, and vegetation (Abate et al 2018 andCampos-Herrera et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The overall recovery rate of the EPNs ( Steinernema and Heterorhabditis ) from soil samples of Northeastern region of Thailand was 7.82%. This result was similar to that reported by Brodie [ 31 ] from Fiji Islands (7.3%), Valadas [ 32 ] from Portugal (6.7%), and Hatting [ 33 ] from South Africa (5%). However, this rate was higher than those reported by Caoili [ 34 ] from the Philippines (2.5%), Majić [ 35 ] from Croatia (2.0%), and Noujeim [ 36 ] from Lebanon (1%).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, none of the isolates of H. indica showed nictating or vigorous jumping behaviour and showed strong directional response to volatile host cues confirming their cruiser behaviour. Even though, the IJ of native isolates of H. indica are longer ( Kour et al, 2020 ) than other isolates of H. indica described in literature, their foraging behaviour is similar to them ( Walia et al, 2008 ). However, this contradicts the finding of Susurluk et al (2003) who reported different foraging behaviour for isolates of same Heterorhabditis spp.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, we provide the ecology of the EPN H. indica isolated from the island of Viti Levu, Fiji. The native isolates of H. indica in this study have been isolated from different climatic zones and diverse habitats ( Kour et al, 2020 ). The isolated population of H. indica have shown some degree of morphometric and genetic variability ( Kour et al, 2020 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation